2001
DOI: 10.1021/jm0102250
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 4-Phenylamino-3-quinolinecarbonitriles as Potent Inhibitors of Src Kinase Activity

Abstract: Subsequent to the discovery of 4-[(2,4-dichlorophenyl)amino]-6,7-dimethoxy-3-quinolinecarbonitrile (1a) as an inhibitor of Src kinase activity (IC(50) = 30 nM), several additional analogues were prepared. Optimization of the C-4 anilino group of 1a led to 1c, which contains a 2,4-dichloro-5-methoxy-substituted aniline. Replacement of the methoxy group at C-7 of 1c with a 3-(morpholin-4-yl)propoxy group provided 2c, resulting in increased inhibition of both Src kinase activity and Src-mediated cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
143
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 22 publications
(90 reference statements)
3
143
0
6
Order By: Relevance
“…Because of this, several small molecule Src inhibitors are in early clinical development (10)(11)(12). Of particular interest is the ability of these inhibitors to block organ-specific metastases (13,18,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this, several small molecule Src inhibitors are in early clinical development (10)(11)(12). Of particular interest is the ability of these inhibitors to block organ-specific metastases (13,18,25).…”
Section: Discussionmentioning
confidence: 99%
“…The Src inhibitor 4-amino-5-(4-chlorophenyl)-7-(1-butyl)pyrazolo [3,4-alpha]pyrimidine decreased tumor growth and metastasis in a xenograft model of pancreatic cancer (9). Other small molecule Src inhibitors are in clinical development (10)(11)(12). Among these, the multikinase inhibitor dasatinib has shown efficacy in several preclinical models, including chronic myelogenous leukemia (CML) and pancreatic and prostate cancer, and is approved for treating imatinib resistant or intolerant CML (2,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14] Like imatinib, nilotinib binds an inactive conformation of BCR-ABL; however, because of an improved topographical fit, binding affinity is increased for ABL kinase but reduced in relative terms for other shared kinase targets, such as platelet-derived growth factor receptor. Compared with imatinib, nilotinib is 10-50-fold more potent in inhibiting proliferation of BCR-ABL-expressing cell lines.…”
Section: Characteristics Of Alternative Bcr-abl Inhibitorsmentioning
confidence: 99%
“…3 An earlier IRIS analysis found that no patient with both a CCyR and MMR at 12 months had transformed to AP/BP at 5 years, compared with 5% of patients with a CCyR but no MMR (P ¼ 0.007). 1,47 Although analyses Table 1 Comparison of the potency and selectivity of imatinib, dasatinib, nilotinib and bosutinib for BCR-ABL in vitro [8][9][10][11][12][13][14] Fold increase in potency against BCR-ABL in cellular proliferation assays relative to imatinib Comparative potency against BCR-ABL, PDGFRb, KIT and SRC based on IC 50 values in proliferation/kinase assays from IRIS and Hammersmith cohorts found no TFS advantage for patients who achieved CCyR and MMR at 18 months compared with patients who achieved CCyR alone, achieving a MMR by 12-18 months in both cohorts significantly reduced the probability of losing CCyR. 1,3,48 Thus, if faster responses and higher response rates can be achieved with alternative strategies, such as more potent BCR-ABL inhibitors, this may improve longer-term outcomes in patients with newly diagnosed CML-CP.…”
Section: Characteristics Of Alternative Bcr-abl Inhibitorsmentioning
confidence: 99%